2020
DOI: 10.1016/j.envpol.2020.115451
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to oil spill spreading using case studies and simulated scenarios

Abstract: Fossil fuels still prevail over other energy sources in the world's consumption energy matrix. Thus, oil transportation and operations over maritime routes have been in high demand for a long time. Although oil spill accidents caused by these activities have reduced significantly over the last few decades, they still cause great concern. From this perspective, this paper presents simulation analyses of oil spill case studies using Telemac-3D hydrodynamic model coupled with an oil model. Hence a location suscep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
0
2
0
1
Order By: Relevance
“…For probability and consequence estimation, after reviewing the classical and state-of-the-art literature reviews by Li et al (2012) and Luo and Shin (2016), it is clear that probability and consequence estimation literature can be classified into four major branches as follows: simulation model (Monteiro et al, 2020), fault tree (Fowler and Sorgard, 2000;Sihombing and Torbol, 2018) and Bayesian network (Haenninen, 2014;Jiang and Lu, 2020) approach for causation probability estimation, formula models for geometrical probability estimation (Fujii and Tanaka, 1971;Pedersen, 2010) and using historical statistical data. In order to analyze whether the general oil port and ship owner can take the liability risk and dig out the problems in current Marine pollution prevention laws, this paper assesses the liability risk in general scene.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For probability and consequence estimation, after reviewing the classical and state-of-the-art literature reviews by Li et al (2012) and Luo and Shin (2016), it is clear that probability and consequence estimation literature can be classified into four major branches as follows: simulation model (Monteiro et al, 2020), fault tree (Fowler and Sorgard, 2000;Sihombing and Torbol, 2018) and Bayesian network (Haenninen, 2014;Jiang and Lu, 2020) approach for causation probability estimation, formula models for geometrical probability estimation (Fujii and Tanaka, 1971;Pedersen, 2010) and using historical statistical data. In order to analyze whether the general oil port and ship owner can take the liability risk and dig out the problems in current Marine pollution prevention laws, this paper assesses the liability risk in general scene.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This model can predict the quality of seawater and the dispersion of a plume pollutant in 1D, 2D, and 3D, taking into account the weather conditions and local currents in a particular area. Several studies were conducted using the TELEMAC model to simulate various hydrodynamic ocean conditions with and without oil spills [20][21][22][23][24][25]. Lopes et al [20] employed the TELEMAC-3D hydrodynamic model coupled with the Easy Coupling Oil System (ECOS) model to simulate oil spill behaviors under different extreme environmental conditions in the Patos Lagoon, located in the southern region of Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…The research study produced important and novel findings on how the interaction of river discharge and tidal range influences oil slick dynamics, which could aid responders in assessing likely oil trajectories and deploying response tools in a cost-effective manner. Monteiro et al [23] noted that the variability of the oceanographic and meteorological conditions are sources of uncertainties in the susceptibility prediction of oil contamination. The authors suggested that the reliability of susceptibility assessments could be improved by incorporating a greater number of oil spill scenarios into the analysis.…”
Section: Introductionmentioning
confidence: 99%
“…It is difficult to imagine the modern world today without the use of crude oil and gas processing products. [1], [2], and also from it you can get plastic, various chemicals, rubber, synthetic fibers and even cosmetics. Therefore, oil is in great demand [3].…”
Section: Introductionmentioning
confidence: 99%